Frequency-dependent effects of EEG phase resetting on reaction time. (November 2021) - Nakatani, Hironori; Kawasaki, Masahiro; Kitajo, Keiichi; Yamaguchi, Yoko
Highlights: Theta-band phase resetting in the left parietal region was linked to reaction time. Delta-band phase resetting in the posterior region was linked to reaction time. Relationship between phase resetting and RT differs between theta and delta bands. Frequency-dependent effects of EEG phase resetting on reaction time was observed. Abstract: There is trial-to-trial variability in the reaction time to stimulus presentation. Since this variability exists even in an identical stimulus condition, it reflects the internal neural dynamics of the brain. To understand the neural dynamics that influence the reaction time, we conducted an electroencephalogram (EEG) experiment in which participants were asked to press a response button as quickly as possible when a stimulus was visually presented. Phase-locking factor analysis revealed that phase resetting in two frequency bands, which appeared 0.2 s after the stimulus presentation, characterized the reaction time. The combination of the theta band phase resetting in the left parietal region and the delta band phase resetting mainly in the posterior region was associated with the fastest reaction time, whereas delta band phase resetting without theta band phase resetting was associated with the faster reaction time. The results indicated that there were frequency-dependent effects in the relationships between the EEG phase resetting and reaction time.